FRAMING WATER SUSTAINABILITY AND TECHNOLOGICAL SOLUTIONS: A MICROSTRUCTURAL ANALYSIS OF RHETORICAL STRATEGIES IN ELON MUSK’S 2024 WORLD WATER FORUM SPEECH - Sari, Puspita Ambar; Suprayogi, Suprayogi (JOURNAL OF LANGUAGE, 2024)
This study provides a detailed microstructural analysis of Elon Musk's 2024 World Water Forum speech, focusing on his use of rhetorical strategies to address critical water sustainability challenges and advocate for technological solutions. By analyzing Musk’s language, tone, and framing techniques, this research uncovers how he skillfully crafts a narrative that combines urgency with optimism, positioning technology as an essential tool for addressing water scarcity. Key findings reveal that Musk employs hyperbole to magnify technology’s potential impact, metaphors to simplify complex concepts, and rhetorical questions to engage his audience in critical reflection. Additionally, he uses repetition to emphasize core themes, reinforcing his message on the importance of collaboration across sectors. The study concludes that Musk’s rhetorical approach is not only informative but also mobilizing, as it seeks to inspire both public and private stakeholders to take active roles in sustainable water management. This research underscores the power of strategic rhetoric in advancing discourse on sustainability and encouraging actionable solutions.